Design of Dashboard Administration of the Public Sector - Samad Samad; Albertus Laurensius Setyabudhi (YCMM, 2023)
This research discusses the design of a public service administration system which is expected to facilitate the processing of public service administration data, the method of implementing activities carried out to achieve the success of the objectives of this activity through mapping indicators and data elements, field surveys, dashboard designs. The results of the design of a public service administration system with the waterfall model stages have resulted in a new system analysis UML modeling approach to systematic and sequential software development starting from the level and progress of the system in analysis, design, code, testing and maintenance of the system, with this system can maximize time and easily find data again.